Pemanfaatan Pati Garut Sebagai Bahan Pengental pada Saus Cabai Keriting dan Rawit - Fadilah Husnun; Amalia L Hasanah; Nanik Suhartatik; Akhmad Mustofa; Efi N Sholihah; Tri Marwati; Titiek F Djaafar; Anna Fajariyah (AGRITEKNO: Jurnal Teknologi Pertanian, 2025)
Chili paste or chili sauce is a popular product among Indonesians. The development of thickening compounds in chili sauce is essential to enhance its functional properties. In the research, an alternative thickening agent for chili sauce will be developed using arrowroot starch. The objective of this research was to analyze physicochemical properties and panelists' acceptance of chili sauce formulated with arrowroot starch as a thickening agent. This research employed an experimental method using a completely randomized design with 2 factors :(1) chili type ratio- 100 g of curly chili: 50 g cayenne chili, 75 g curly chili: 75 g cayenne chili, 50 g curly chili: 100 g cayenne chili, and (2) cooking duration at 3 levels - 15, 30 and 45 minutes. The observed parameters included moisture content, ash content, viscosity, antioxidant activity, total flavonoid content, color, pH, total soluble solids, total titratable acidity, and sensory hedonic attributes. The results showed that the optimal formulation was obtained in the K2T2 treatment (75 g curly chili: 75 g cayenne pepper with a cooking time of 30 minutes). The chili sauce exhibited a moisture content of 69.46%, ash content of 3.45%, viscosity of 160 dPas, total flavonoid content 0.84 mg/g, antioxidant activity of 15.96%. The color ranged from red to orange, with a pH of 4.83, total titratable acidity of 0.06%, and total soluble solids 22%°Brix. Sensory evaluation scores indicated good panelist acceptance with ratings for color 3.53, aroma 3.93, taste 3.67, viscosity 4.07, and overall liking 4.73. These findings suggest that arrowroot starch is a promising thickening agent for chili sauce production, particularly with a 30-minute cooking time. Moreover, the characteristics of the developed chili sauce were not significantly different from those of commercial chili sauces.